1871 Revision of the Statutes of New Jersey 263, An act relating to the transportation of explosive and dangerous material, § 1 - (:unkn) unknown (General Publisher, 1874)
That if any person shall deliver, or cause to be delivered, to any canal, railroad, steamboat, or other transportation company, or to any persons, firm, or corporation engaged in the business of transportation, any nitroglycerine, dualin, dynamite, gunpowder, mining or blasting powder, gun-cotton, phosphorous, friction matches, or other explosive or dangerous material of any nature whatsoever, under any false or deceptive invoice or description, or without previously informing such person, firm or corporation, in writing, of the true nature of such article, and without having the box, keg, barrel, can or package containing the same plainly marked with the name of the explosive or dangerous material therein contained, such person shall be guilty of a misdemeanor, and upon conviction thereof shall be sentenced to imprisonment for thirty days, and to pay a fine of one hundred dollars, and shall be responsible for all damages to persons or property directly or indirectly resulting from the explosion of any such article. § 2. That it shall and may be lawful for any officer or agent of any person, firm, or corporation, engaged in the business of transportation to require any package tendered for transportation, believed to contain explosive material, to be opened by the person delivering the same, and to refuse to receive any such package unless such requirements be complied with; and if such package be opened and found to contain such explosive or dangerous material, the said package and its contents shall be forthwith removed to any lawful place for the storing of gun-powder, and after conviction of the offender, or after three months from such removal, the said package, with its contents, shall be sold at public sale, after the expiration of ten days from notice of the time and place of such sale, published in one newspaper in the county where such seizure shall have been made; and the proceeds of such sale, after deducting therefrom the expenses of removal, storage, advertisement, and sale, shall be paid into the treasury of the said county; provided, however, that nothing in this act contained shall be construed to require common carriers to transport any such explosive or dangerous articles against their consent, nor to transport them otherwise than at such times, and under such regulations for safety to persons and property, as they may from time to time prescribe in relation thereto
--
Keywords: GUN POWDER TRANSPORTATION